Improving Efficiency through Consolidation of Jurisdictions? Evidence from the Cantons of Switzerland - Widmer, Philippe K.; Elias, George; Zweifel, Peter (Raumforschung und Raumordnung | Spatial Research and Planning, 2013)
The purpose of this paper is to analyze the optimal scale of local jurisdictions (cantons) in Switzerland applying Data Envelopment Analysis to the years 2000–2004. Aggregate output performance indicators for four local government activities (administration, education, health, and transportation) are used to measure technical and scale efficiency and to derive Data Envelopment Analysis scores. Results show that these public services fail to exhibit economies of scale, undermining quests for centralization of public good provision while suggesting the possibility of Tiebout competition.